Employee voice: speaking up in organisation as a correlate of employee productivity in oil and gas industry - an empirical investigation from Nigeria - Akinwale, Olusegun Emmanuel (Serbian Journal of Management, 2019)
The understanding and interpretation of voice have been given critical attention among researchers, practitioners in recent years. The firm believes of the workforce that they can openly express their personal opinion and concerns to higher authority in the organisation, and who believe that they can influence the decision, are likely to demonstrate optimistic attitude and constructive behaviours. The study surveyed 1067 employees of Nigerian oil and gas and 902 respondents were returned and used for the study. Data were obtained from the participants using a questionnaire of 19 question items by means of probability sampling strategy, while the research design was cross-sectional. The findings of the study indicate a coherent and consistent one with literature. The study employed eight dimensions as drivers of employee voice in the Nigeria oil and gas industry which discovered mixed outcomes. One of the drivers is the communication/exchange of views which had an inverse association with employee productivity.  Employee collective representation and employee engagement also recorded an insignificant relationship with employee productive work behaviour. However, employee participation, improved management systems, employee supervisor-subordinate relationship, workforce contribution and upward problem solving were significantly correlated with employee productive work behaviour. The study used descriptive statistics and Pearson moment correlation in analysing the data gathered from the participants and concluded that workforce of Nigerian oil and gas are not deeply engaged with the workplace environment due to the observed challenge of not allowing them to be duly represented and discourage them from exchanging their views and ideas.